Advancing hematite photoanodes for photoelectrochemical water splitting: the impact of g-C3N4 supported Ni-CoP on photogenerated hole dynamics - Yang,M; Oldham,L; Daboczi,M; Baghdadi,Y; Cui,J; Benetti,D; Zhang,W; Durrant,JR; Hankin,A; Eslava,S (Advanced Energy Materials, 2024)
The increasing demand for clean hydrogen necessitates the rapid development of efficient photoanodes to catalyze the water oxidation half-reaction effectively. Here a strategy is introduced to fabricate photoanodes that synergistically combine and leverage the properties of porous Ti-doped hematite (Ti-Fe2O3) and graphitic carbon nitride (g-C3N4) nanosheets anchored with in situ grown Ni-doped CoP co-catalyst (Ni-CoP). The resulting hybrid photoanodes exhibit >7 times higher photocurrent density at +1.23 VRHE compared with Ti-Fe2O3 photoanodes. Comprehensive characterization techniques, including ambient photoemission spectroscopy, intensity-modulated photocurrent spectroscopy, and transient absorption spectroscopy complementarily reveal the key impact of g-C3N4 in these composites with enhanced solar oxygen evolution reaction: The incorporation of g-C3N4 leads to enhanced charge separation through a type-II heterojunction, thereby increasing the hole flux at the surface, and extending the charge carrier lifetime to the ms-s range needed for water oxidation. Additionally, g-C3N4 facilitates efficient transfer of photogenerated holes to the fine Ni-CoP nanoparticles confined in the graphitic matrix for a boosted oxygen evolution reaction. These findings highlight the advantages of complex heterostructure photoanodes and demonstrate a new application of g-C3N4 as a multifunctional support of co-catalysts for future photoanodes with enhanced performance.